Follicular scales, scalp and ocular involvement in patients with papulopustular rosacea: prevalence and association with Demodex mite proliferation - Ilaria Trave; Emanuele Cozzani; Ilaria Salvi; Aurora Parodi (PAGEPress Publications, 2023)
Facial follicular scales, dandruff, scalp itching and ocular alterations are lesser-known signs of rosacea and demodicosis. The aim of this prospective original study was to investigate the presence of these signs and symptoms in patients with almost-clear, mild and moderate papulopustular rosacea and to study the differences between Demodex-positive and Demodex-negative rosacea. Twenty-seven out of 60 patients (45%) presented follicular scales, 24 (40%) ocular involvement and 22 (36.67%) scalp involvement. Follicular scales were more frequently observed in mild and moderate than in almost-clear rosacea (p<0.001). Itching of the scalp was more frequently reported in patients with moderate rosacea than in those with mild disease (p=0.05). Follicular scales (p=0.002) and scalp itching (p=0.05) were more frequently reported in Demodex-positive than in Demodex-negative patients. Among Demodex-positive patients, scalp itching was more frequently reported in mild than in almost clear rosacea (p=0.01) and ocular symptoms associated to scalp itching were more frequently reported in moderate than in almost-clear rosacea (p=0.05). We suggest looking for these signs and symptoms in all patients with papulopustular rosacea, because they can be a sign of a more severe form of rosacea or of demodicosis.